The Influence of Leadership and School Culture on the Performance of State SMP Teachers in Sungai Pinang Subdistrict, Ogan Ilir Regency - Minayarni, Minayarni; Ahmad, Syarwani; Wahidy, Achmad (Jurnal Pendidikan Tambusai, 2021)
This research aims to determine the influence of leadership and school culture on teacher performance of junior high school in Sungai Pinang Subdistrict, Ogan Ilir Regency. The sample was 54 teachers of State SMP. This type of research is quantitative research. While the research method used is a descriptive quantitative method. Data collection techniques using questionnaires, observations and documentation. While data analysis techniques using t test and F test. The results of this reaserch can be concluded that there is an influence of leadership and school culture on the performance of public junior high school teachers in Sungai Pinang Subdistrict Ogan Ilir both partially and simultaneously